Influence of Wheelchair Type on Kinematic Parameters in Wheelchair Rugby - Sadate Bakatchina; Thierry Weissland; Florian Brassart; Ilona Alberca; Opale Vigie; Didier Pradon; Arnaud Faupin (Frontiers in Sports and Active Living, 2022)
IntroductionIn wheelchair rugby, players use either an offensive or defensive wheelchair depending on their field position and level of impairment. Performance of wheelchair rugby players is related to several parameters, however it is currently unclear if differences in performance are related to wheelchair type or no: the effect of wheelchair type on performance variables has not been evaluated. The aim of this study was to compare offensive and defensive wheelchairs on performance variables during a straight-line sprint.MethodsThirteen able-bodied people performed two 20 m sprint trials: one with an offensive and one with a defensive wheelchair. Data were collected using inertial measurement units fixed on the wheelchair. Peak wheelchair velocities and left-right asymmetries in peak wheel velocities were measured during the acceleration and constant peak velocity phases. Sprint time, cycle frequency, and mean and maximum velocity were calculated over the entire sprint.ResultsThe peak velocities of the first 2 pushes (acceleration phase) were significantly higher with the defensive than the offensive wheelchair (p < 0.04 and p < 0.02). Mean and maximum sprint velocity were significantly higher (p < 0.03 and p < 0.04, respectively) with the defensive wheelchair. Cycle frequency and asymmetry did not differ between wheelchairs.ConclusionPerformance was higher with the defensive than the offensive wheelchair, suggesting that the frequent finding that the higher performance of offensive as compared to defensive players is not related to the use of an offensive wheelchair.